Lost time: COVID‐19 indemnity claim reporting and results in the Wisconsin workers' compensation system from March 12 to December 31, 2020. Issue 12 (25th October 2022) - Modji, Komi K. S.; Morris, Collin R.; Creswell, Paul D.; McCoy, Katherine; Aiello, Tracy; Grajewski, Barbara; Tomasallo, Carrie D.; Pray, Ian; Meiman, Jonathan G.
Abstract: Background: The COVID‐19 pandemic introduced a new compensable infectious disease to workplaces. Methods: This was a descriptive analysis of Wisconsin COVID workers' compensation (WC) claims between March 12 and December 31, 2020. The impact of the presumption law (March 12 to June 10, 2020) was also evaluated. Results: Less than 1% of working‐age residents with COVID‐19 filed a claim. COVID‐19 WC claim rates (per 100, 000 FTE) were notably low for frontline industry sectors such as Retail Trade ( n  = 115), Manufacturing ( n  = 88), and Wholesale Trade ( n  = 31). Healthcare workers (764 claims per 100, 000 FTE) comprised 73.2% of COVID‐19 claims. Most claims (52.8%) were denied and the proportion of denied claims increased significantly after the presumption period for both first responders and other occupations. Conclusion: The presumption law made benefits accessible primarily to first responders. Further changes to WC systems are needed to offset the individual and collective costs of infectious diseases.